Abdominal aortic calcification: from ancient friend to modern foe. (29th April 2020) - Bartstra, Jonas W; Mali, Willem P Th M; Spiering, Wilko; de Jong, Pim A
Abstract: Background: Abdominal aortic calcifications were already ubiquitous in ancient populations from all continents. Although nowadays generally considered as an innocent end stage of stabilised atherosclerotic plaques, increasing evidence suggests that arterial calcifications contribute to cardiovascular risk. In this review we address abdominal aortic calcification from an evolutionary perspective and review the literature on histology, prevalence, risk factors, clinical outcomes and pharmacological interventions of abdominal aortic calcification. Design: The design of this study was based on a literature review. Methods: Pubmed and Embase were systematically searched for articles on abdominal aortic calcification and its synonyms without language restrictions. Articles with data on histology, prevalence, risk factors clinical outcomes and/or pharmacological interventions were selected. Results: Abdominal aortic calcification is highly prevalent in the general population and prevalence and extent increase with age. Prevalence and risk factors differ between males and females and different ethnicities. Risk factors include traditional cardiovascular risk factors and decreased bone mineral density. Abdominal aortic calcification is shown to contribute to arterial stiffness and is a strong predictor of cardiovascular events and mortality. Several therapies to inhibit arterial calcification have been developed and investigated in small clinical trials. Conclusions: Abdominal aortic calcification is from all eras and increasingly acknowledged as an independent contributor to cardiovascular disease. Large studies with long follow-up must be carried out to show whether inhibition of abdominal aortic calcification will further reduce cardiovascular risk.